Ultrastructural characteristics of the follicle cell-oocyte interface in the oogenesis of Ceratophrys cranwelli - Villecco, Evelina I. (2002)
In this work we carried out an ultrastructural analysis of the cell interface between oocyte and follicle cells during the oogenesis of the amphibian Ceratophrys cranwelli, which revealed a complex cell-cell interaction. In the early previtellogenic follicles, the plasma membrane of the follicle cells lies in close contact with the plasma membrane of the oocyte, with no interface between them. In the mid-previtellogenic follicles the follicle cells became more active and their cytoplasm has vesicles containing granular material. Their apical surface projects cytoplasmic processes (macrovilli) that contact the oocyte, forming gap junctions. The oocyte surface begins to develop microvilli. At the interface both processes delimit lacunae containing granular material. The oocyte surface has endocytic vesicles that incorporate this material, forming cortical vesicles that are peripherally arranged. In the late previtellogenic follicle the interface contains fibrillar material from which the vitelline envelope will originate. During the vitellogenic period, there is an increase in the number and length of the micro- and macrovilli, which become regularly arranged inside fibrillar tunnels. At this time the oocyte surface exhibits deep crypts where the macrovilli enter, thus increasing the follicle cell-oocyte junctions. In addition, the oocyte displays coated pits and vesicles evidencing an intense endocytic activity. At the interface of the fully grown oocyte the fibrillar network of the vitelline envelope can be seen. The compact zone contains a fibrillar electrondense material that fills the spaces previously occupied by the now-retracted microvilli. The macrovilli are still in contact with the surface of the oocyte, forming gap junctions.